Emission of fibres and atmospheric pollutants from the thermal treatment of asbestos containing waste (ACW). (20th September 2020) - Tomassetti, Laura; Di Giuseppe, Dario; Zoboli, Alessandro; Paolini, Valerio; Torre, Marco; Paris, Enrico; Guerriero, Ettore; Petracchini, Francesco; Gualtieri, Alessandro F.
Abstract: Asbestos containing materials (ACMs) are currently landfilled or encapsulated, but this may lead to the release of fibres in the environment. Hence, the destruction of asbestos containing waste (ACW) is now regarded as a preferable option. Thermal treatments based on chrysotile and amphibole asbestos dehydroxylation and recrystallization are being successfully developed for this purpose. This study investigates the emission of asbestos fibres from a prototype for asbestos treatment. Other atmospheric pollutants measured include carbon monoxide (CO), nitrogen oxides (NOx ), sulfur dioxide (SO2 ), volatile organic compounds (VOCs), heavy metals, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) dioxins and furans (PCDD/Fs). Both cement-asbestos and ACM containing polyurethane were tested. No asbestos fibres were found, neither in the emission nor in the solid residue. The concentration of NOx, SO2 and heavy metals are comparable with municipal solid waste incinerators (MSWI) and cement plants. PAHs, BTEX (benzene, toluene, ethylbenzene, xylenes) and styrene are higher in the presence of polyurethane. The presence of polyvinyl chloride (PVC) in the coating of asbestos cement can increase the emission of halogenated VOCs, PCBs and PCDD/Fs. Our results confirm that asbestos inertisation is a safe process for the environment and human health, and economically competitive with landfills. Graphical abstract: Image 1 Highlights: First measurement of atmospheric pollutants emitted from ACW treatment. Experimental evidence that no asbestos fibres are emitted in the atmosphere. Chrysotile dehydroxylation/recrystallization in byproduct and emitted particles. PAHs and BTEX mainly due to polyurethane and other non-asbestos components of ACW. PVC in ACW coating promotes the emission of dioxins and halogenated VOCs.